Delirium, Dementia, and In-Hospital Mortality: The Results From the Italian Delirium Day 2016, A National Multicenter Study. (4th July 2018) - Morandi, Alessandro; Di Santo, Simona G; Zambon, Antonella; Mazzone, Andrea; Cherubini, Antonio; Mossello, Enrico; Bo, Mario; Marengoni, Alessandra; Bianchetti, Angelo; Cappa, Stefano; Fimognari, Filippo; Antonelli Incalzi, Raffaele; et al.
Abstract: Background: There is little evidence about the prevalence of cognitive disorders and their effect on in-hospital mortality in large multicenter studies. The objectives of the 2016th edition of the "Italian Delirium Day, " a large multicenter study on in-hospital older patients, were to assess (i) the point prevalence of cognitive impairment/no dementia, dementia, delirium, and delirium superimposed on dementia and (ii) the effect of these conditions on in-hospital mortality. Methods: This multicenter study and included 2, 037 older patients (aged ≥65 years) admitted to acute medical and surgical wards across 205 acute hospitals. The four cognitive disorders groups were defined with a structured approach including the four AT and the presence of a documented diagnosis of dementia. The outcome measure was in-hospital mortality, as reported by the researchers involved in the study in each center. Results: The mean age was 81.17 ± 7.7 years. Overall, 893 patients (43.8%) had neither delirium nor dementia nor cognitive impairment, 483 (23.7%) had cognitive impairment/no dementia, 230 (11.3%) dementia alone, 187 (9.2%) delirium alone, and 244 (12.0%) delirium superimposed on dementia. Overall, 99 (4.8%) patients died. Participants with delirium alone (odds ratio 2.56; 95% confidence interval: 1.29–5.09) and those with delirium superimposed on dementia (odds ratio 2.60; 95% confidence interval: 1.39–4.85) had higher mortality risk compared with the reference group of patients with "no cognitive impairment." Conclusions: Delirium and delirium superimposed on dementia were highly prevalent among older hospitalized patients and significantly increased in-hospital mortality. Clinicians should systematically assess these conditions and recognize them as markers of critical conditions and predictors of imminent death.